The Effects of Odd or Even Number of Options on The Variance of Item Validity in Environmental Personality (Big-Five Personality) - Rahmirini Datau; I Made Putrawan; Wardani Rahayu (International Journal of Science and Society, 2022)
Validity is one of the important characteristics in any psychological measuring tool. Measurement tools in his research more generally include a variety of observations and usually include responses that aim to regulate and limit the choices available to respondents and assessments. There are many studies that have assessed how the number of response options on a scale affects validity and reliability, but fewer have discussed whether the midpoint should be included as a response option, or whether the scale is even. Regardless of where the response scale is in psychological measurements, the environmental personality (big-five personality) scale has been expanded and elaborated in various ways in previous research since the introduction of dreams. The big-five personality model is the most extensive model for measuring environmental personality. This study aims to determine whether there is a difference between the number of odd and even option scales on the validity variance of students' environmental personality (big-five personality) items, and to see which scale of the number of options is better or suitable for the environmental personality (big-five personality) instrument. The calculation data were analyzed using the one-way ANOVA method. The results of this study indicate that the scale of the number of odd options (five options) and the scale of the number of even options differ significantly in the variance of the validity of the environmental personality items (big-five Personality). The mean plot results show that the odd option scale higher than the even scale. This research can be carried out for further research in using the odd scale on the environmental personality measurement tool (Big-five Personality) with the expansion being studied.